2013
DOI: 10.1177/0018726712464802
|View full text |Cite
|
Sign up to set email alerts
|

The nuanced nature of work quality: Evidence from rural Newfoundland and Ireland

Abstract: This article explores the relationship between job and work quality and argues that while it is important to examine job quality, to understand workers' experiences fully, the focus should be on the broader concept of work quality which places the job against its wider socioeconomic context. Based on the experiences of 88 rural workers gathered via interviews in Newfoundland and Ireland, it appears that the same or similar jobs can be regarded very differently depending upon the context in which they are embed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 43 publications
1
44
0
2
Order By: Relevance
“…Individuals, he observes, trade off good matches in some dimensions to avoid mismatch in others with adverse impacts for individuals and organisations. Evaluating against a single measure of a good job may fail to reflect this: it ignores the personal nature of the construct and the extent to which it is influenced by individual experiences, life goals and by the standards of the community to which workers compare themselves (Cooke, Donaghey and Zeytinoglu 2013).…”
Section: Individual Preferencementioning
confidence: 99%
See 2 more Smart Citations
“…Individuals, he observes, trade off good matches in some dimensions to avoid mismatch in others with adverse impacts for individuals and organisations. Evaluating against a single measure of a good job may fail to reflect this: it ignores the personal nature of the construct and the extent to which it is influenced by individual experiences, life goals and by the standards of the community to which workers compare themselves (Cooke, Donaghey and Zeytinoglu 2013).…”
Section: Individual Preferencementioning
confidence: 99%
“…However, there is also an argument that good quality work can have a positive influence on health. This includes the contribution which purposeful activity and striving against adversity makes to happiness (Warr 2007b), the significance of social relationships (Cooke, Donaghey and Zeytinoglu 2013) and the health benefits of physical activity at work (Straker and Mathiassen 2009). A substantial literature review by Waddell and Burton (2006) confirmed the health benefits of employment (compared to unemployment) and more recent work by Sahlgren (2013) demonstrated net benefits of remaining in work compared to retirement.…”
Section: The Relationship Between Work and Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Green 2006Green , 2008Gallie et al 2004;Holman 2013). The recent literature also increasingly captures subjective components of jobs through its attentiveness to workers' choices, values, and constraints (see Cooke et al 2013), in particular job satisfaction, employee work preferences and perceived fulfillment (Clark 2005;Tsitsianis and Green 2006;Brown et al 2007;Bustillo et al 2009). The broadest typologies therefore capture job quality in relation to individuals' life stages, values, and opportunities.…”
Section: Multi-dimensional Models Of Good Jobsmentioning
confidence: 99%
“…A key difficulty when measuring job quality then, is that there is 'no international agreement as to what job quality is and how it might be measured' (Muñoz de Bustillo et al, 2011). In addition to international and cultural differences in perceptions of what contributes to good quality work (Wallace et al, 2007), there are also differences between individuals, influenced by factors such as age, gender and various personality attributes (see Warr (2007) for a review), as well as personal and socioeconomic circumstances (Cooke et al, 2013;Loughlin and Murray, 2013).…”
Section: Introductionmentioning
confidence: 99%